Communication: Mode specific quantum dynamics of the F + CHD3 → HF + CD3 reaction - Qi, Ji (2016)
The mode specific reactivity of the F + CHD3 → HF + CD3 reaction is investigated using an eight-dimensional quantum dynamical model on a recently developed ab initio based full-dimensional potential energy surface. Our results indicate prominent resonance structures at low collision energies and absence of an energy threshold in reaction probabilities. It was also found that excitation of the C-D stretching or CD3 umbrella mode has a relatively small impact on reactivity. On the other hand, the excitation of the C-H vibration (v1) in CHD3 is shown to significantly increase the reactivity, which, like several recent quasi-classical trajectory studies, is at odds with the available experimental data. Possible sources of the disagreement are discussed.